Interferon response in normal and Aleutian disease virus-infected mink. - Wiedbrauk, D L (1986)
Studies were done to determine whether differences in interferon production are responsible for the resistance of pastel mink to Aleutian disease. The abilities of normal pastel and sapphire mink to produce interferon when inoculated with either Newcastle disease virus or a synthetic polyribonucleotide, poly (I):poly (C), were identical, even to the production of a novel, acid-labile interferon. The resistance of pastel mink to Aleutian disease did not correlate with interferon production, because neither sapphire nor pastel mink produced detectable amounts of interferon when infected with either the Pullman strain of Aleutian disease virus (ADV) or the highly virulent Utah I strain. Sapphire mink infected with the Pullman strain responded normally to poly (I):poly (C) early in the course of the disease, but interferon production was impaired late, when the mink were hypergammaglobulinemic and had renal, vascular, and hepatic lesions. These data suggest that ADV Pullman neither stimulates nor interferes with interferon production in infected mink and may represent a mechanism whereby ADV can more readily establish infection.